Quality Of Life Of Patients With Chronic Obstructive Pulmonary Disease Based On Clinical Phenotypes - Ng, Diana Leh-Ching; Liam, Chong Kin; Pang, Yong Kek; Chai, Chee Shee; Poh, Mau Ern; Wong, Chee Kuan; Tan, Jiunn Liang (Wiley Online Library, 2018)
Background and Aims: Spanish chronic obstructive pulmonary disease (COPD) guideline classifies COPD into 4 clinical phenotypes: nonexacerbator (A), asthma-COPD overlap (B), exacerbator with emphysema(C) and exacerbator with bronchitis (D).